Theoretical and methodological principles of self-education of future teachers in the process of the modernization of higher pedagogical education - Пономарьова, Г. Ф. (Scientific notes of the pedagogical department, 2018)
The article reveals the main theoretical and methodological principles of self-education of future teachers taking into account the modern tendencies towards the modernization of higher pedagogical education. Specific features of self-education as a factor of the development of the future teacher’s personality are defined, methods and forms are characterized. It is determined self-education completes the process of education of the future teacher’s personality, after all it will be actual at all subsequent stages of self-development and self-improvement. This research notes the ability to adapt, to orient in unforeseen life situations, to solve conflict relationships, not lose themselves in extreme life situations. This is not a complete list of tasks solved by self-education. The specific features of self-education as a factor of the development are characterized. They lie in the fact that to the greatest extent self-education based on the individual characteristics of the young person, his or her inclinations and needs. All these indicated facts in their turn give an opportunity to the personality to demonstrate own abilities maximally. They can determine the whole way of personality’s life; ensure the effective realization of physical, intellectual, aesthetic, and moral potencies in the future. The author determines one of the most productive methods of self-education is reflection, which means the process of thinking and consideration of the individual about events, phenomena, states, and properties in own consciousness of personality. Reflexion assumes not only the cognition of a person himself or herself in a certain situation or a certain period, but also an understanding of the attitude of social environment towards the personality, as well as the development of ideas about the changes that may occur with individual. The experience of the Municipal Establishment «Kharkiv Humanitarian and Pedagogical Academy» Kharkiv Regional Council for stimulating of self-education of students as future teachers is thoroughly covered. It is noted that the system of self-education of student youth at the Academy is realized in the program «The Ideal of a Modern Teacher». This program contains such stages as self-knowledge, self-orientation, self-design, self-organization, self-mobilization, self-motivation, self-communication, self-formation, self-control, self-analysis, self-evaluation, and self-correction.